Cerebral sterile inflammation in neurodegenerative diseases - Kento Otani; Takashi Shichita (BMC, 2020)
Abstract Therapeutic strategies for regulating neuroinflammation are expected in the development of novel therapeutic agents to prevent the progression of central nervous system (CNS) pathologies. An understanding of the detailed molecular and cellular mechanisms of neuroinflammation in each CNS disease is necessary for the development of therapeutics. Since the brain is a sterile organ, neuroinflammation in Alzheimer's disease (AD), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS) is triggered by cerebral cellular damage or the abnormal accumulation of inflammatogenic molecules in CNS tissue through the activation of innate and acquired immunity. Inflammation and CNS pathologies worsen each other through various cellular and molecular mechanisms, such as oxidative stress or the accumulation of inflammatogenic molecules induced in the damaged CNS tissue. In this review, we summarize the recent evidence regarding sterile immune responses in neurodegenerative diseases.